2013
DOI: 10.1155/2013/148468
|View full text |Cite
|
Sign up to set email alerts
|

Maltreatment‐Associated Psychiatric Problems: An Example of Environmentally Triggered ESSENCE?

Abstract: This paper presents a new concept—maltreatment associated psychiatric problems (MAPP)—a syndrome of overlapping complex neurodevelopmental problems in children who have experienced abuse or neglect in early life. Children with MAPP are a hidden population in the community and, in clinical settings, their problems can seem overwhelming. Individual disorders associated with maltreatment are discussed as well as the overlap between these disorders and their shared environmental and genetic predisposing factors. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Gilberg (2010) suggested that a child with an Attachment Disorder may also display the symptoms of ADHD and depression, for example, and importantly these should not be looked upon in isolation. Minnis (2013) Rutter, Giller and Hagell (1998). Here it was suggested that many boys who experienced harsh, physically or verbally abusive punitive parenting could develop conduct disorder and violent criminal behaviour in later years.…”
Section: Attachment Disorder Maltreatment Mental Health and Offendingmentioning
confidence: 99%
“…Gilberg (2010) suggested that a child with an Attachment Disorder may also display the symptoms of ADHD and depression, for example, and importantly these should not be looked upon in isolation. Minnis (2013) Rutter, Giller and Hagell (1998). Here it was suggested that many boys who experienced harsh, physically or verbally abusive punitive parenting could develop conduct disorder and violent criminal behaviour in later years.…”
Section: Attachment Disorder Maltreatment Mental Health and Offendingmentioning
confidence: 99%
“…Dyadic Developmental Psychotherapy (DDP) is the only intervention that we are aware of that incorporates all of the elements suggested by the literature for the treatment of MAPP [ 10 , 11 ]. It is based on the premise that child development is dependent upon, and highly influenced by, the nature of the parent–child relationship and that development of this relationship requires ongoing, dyadic (reciprocal) experiences between parent and child.…”
Section: Introductionmentioning
confidence: 99%
“…Young children coming into foster care are at a high risk of having overlapping problems and should all be considered as potential cases with Maltreatment-Associated Psychiatric Problems (MAPP) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Minnis [ 15 ] recently described a new concept: Maltreatment-Associated Psychiatric Problems (MAPP), a syndrome of overlapping complex neurodevelopmental problems in children who have experienced abuse or neglect in early life. Minnis argues that the early life events these children face place them at an increased risk of developing problems and that when problems do arise in the context of maltreatment, they are likely to be complex and overlapping.…”
Section: Introductionmentioning
confidence: 99%